2013
DOI: 10.1038/jcbfm.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variability of Resting Cerebral Blood Flow in Healthy Subjects: A Study Using 133Xe SPECT Measurements

Abstract: Measurements of cerebral blood flow (CBF) show large variability among healthy subjects. The aim of the present study was to investigate the relative effect of established factors influencing CBF on the variability of resting CBF. We retrospectively analyzed spontaneous variability in 430 CBF measurements acquired in 152 healthy, young subjects using 133 Xe single-photon emission computed tomography. Cerebral blood flow was correlated positively with both end-tidal expiratory P CO 2 (P ET CO 2 ) and female gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
5
41
0
Order By: Relevance
“…This phenomenon could be explained by~10% lower hemoglobin and heamatocrit levels in women, combined with the hypothesis that CBF is regulated to maintain constant oxygen delivery across different hemoglobin levels. 34,35 Our study showed a strong association between resting GM CBF and general cognitive functioning measured by multiple psychometric test scores. This association was not expected and it appears to be reported in only one other study.…”
Section: Discussionmentioning
confidence: 95%
“…This phenomenon could be explained by~10% lower hemoglobin and heamatocrit levels in women, combined with the hypothesis that CBF is regulated to maintain constant oxygen delivery across different hemoglobin levels. 34,35 Our study showed a strong association between resting GM CBF and general cognitive functioning measured by multiple psychometric test scores. This association was not expected and it appears to be reported in only one other study.…”
Section: Discussionmentioning
confidence: 95%
“…Given that hematocrit and gender are important predictors of CBF (Liu et al 2012; Henriksen et al 2014; Henriksen et al 2013), and hematocrit is significantly different between the two genders (p ≤ 0.001, in the current study), Pearson correlation was performed between each variable (hematocrit or gender) and CBF in order to determine which one is the most sensitive predictor of CBF. Hematocrit ( r = −0.39 , p ≤ 0.001) but not gender ( r = 0.18, p = 0.14) was negatively correlated with CBF, thus hematocrit was used as a confounder in the subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As spontaneous fluctuations in PaCO 2 have been shown to introduce within‐subject variability of CBF measurements, the possible influence of PaCO 2 fluctuations were investigated by including the difference in PaCO 2 (PaCO2 PCM – PaCO2 PET ) as a covariate in a multiple regression model with CBF PCM as the dependent variable and CBF PET as the independent variable.…”
Section: Methodsmentioning
confidence: 99%